Pain and the perception of space in fibromyalgia - Michele Scandola; Maddalena Beccherle; Enrico Polati; Giorgia Pietroni; Elena Rossato; Vittorio Schweiger; Valentina Moro (Scientific Reports)
Abstract The Economy of action hypothesis postulates that bodily states rescale the perception of the individual’s environment’s spatial layout. The estimation of distances and slopes in navigation space (i.e. the space reachable by locomotion) is influenced by sensations relating to body condition and the metabolic cost of the actions. The results of the studies investigating the impact of pain on distance estimation remain inconclusive. 28 women suffering from chronic pain and fibromyalgia (FM), and 24 healthy women (HC) were assessed for musculoskeletal, neuropathic, and visceral pain by means of the Widespread Pain Index, the Symptom Severity Scale and an ad-hoc devised questionnaire for pain (the Verona Pain Questionnaire). In a VR-mediated task, they observed a 3D scenario and estimated the distance of a flag positioned at different distances (1, 2, 3, 4 or 5 m) on virtual ramps with either a 4% or 24% inclination in two different conditions: sitting and standing. Overestimation of distances in the steeper ramp condition was expected, if participants executed the task by internally simulating the movement. The results showed a dissociation between the effects of musculoskeletal and visceral-neuropathic pain on distance estimations. While, according to the Economy of Action hypothesis, the HCs estimated the distances as being farther away when the ramp was more inclined (i.e. with a 24% inclination), there was no effect related to the different ramp inclinations in the FM group. Furthermore, visceral and neuropathic pain were found to affect the performance of the FM group. These results suggest that chronic and widespread pain conditions, that typically characterize fibromyalgia, can affect space representations. In line with the Economy of Action hypothesis, bodily based estimation of distances is compromised in these patients.